CT&I e Desenvolvimento Regional: os desafios da região Sul no contexto da economia globalizada do aprendizado - Ivo M. Theis (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2005)
The aim of this article is to contribute to the debate on Science, Technology and Innovation in the broader context of the globalized learning economy, but regarding the challenges that the subject represents to the territorial development of the Brazilian Southern Region. Three main dimensions are on the base of the approach of the question: the first refers to the new economy, supposed characterized by the prevalence of knowledge, but which will here be called learning economy; the second corresponds to the technology, considered not merely as a tool, but in terms of the social, economic and political context in which it is both created and appropriated; the third concerns to the territory understood in a wider, multidimensional and multi-scale sense. Reflecting on the challenges represented by ST&I to the territorial development of Southern Brazil, and even allowing that knowledge became so meaningful in the now existing society, the article is an attempt to make a counterpoint to the optimism which dominates the debate on the theme.